MEANING REPRESENTATION OF CORONA AND COVID-19 IN ONLINE NEWSPAPER - Nida, Faridatun; Zaidi, Ahmad; Dhiyaulhaq, Sahira (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2021)
Corona and COVID-19 become the headline of almost all newspaper articles. It leads to a curiosity of its accordance to World Health Organization naming policy since those terms are relatively new for Indonesian people. Reading the newspaper becomes the solution for updating the condition of the pandemic. Unfortunately, some of the most-frequently-read newspaper seems inconsistent in giving the name that makes them have different references. This research is aimed to see the use of corona and COVID-19 in news articles to see its accordance with WHO naming policy. The analysis was done using AntCont software to see the collocation of corona and covid; besides that, the theory of discourse pragmatic is used to interpret each term's meaning. The analysis reveals that the meaning interpreted in those newspapers is inconsistent for its collocation, conjunction, and writing style. The analysis and its result are expected to evaluate the newsmaker or news writer about giving the reader accurate information. It is also expected to give the reader understanding of the proper meaning of corona and covid